Going beyond Preservation: How to Support Technology-Enhanced Learning in ICH Education. Issue 1 (March 2015) - Pozzi, F.; Alivizatou, M.; Dagnino, F. M.; Ott, M.
The issue of protection and promotion of cultural heritage has become a central topic of European and international cultural policy, especially in recent decades. Beside more 'tangible' cultural manifestations (like archaeological sites, natural parks or museum collections) there is a huge heritage, made up of intangible live expressions like performing arts, social practices, oral traditions, etc. which is threatened by the globalization process. The i-Treasures project looks at some of these intangible cultural expressions with the aim not only of preserving them, but also of providing innovative solutions to education in this field. In order to do this, the project explores the potential of cutting edge technologies for capturing the specificities of the considered Intangible Cultural Heritage (ICH) expressions, analyzing and modeling data and making these resources available for preservation, research and educational purposes. With this aim an open and extendable platform is developed in the project framework. This paper deals with the process of user and system requirements definition and explains how this was necessarily influenced by the specificities of the ICH expressions considered. This process encompassed the identification of the specificities of rare traditional know-how, the discovery of the existing teaching and learning practices and finally the identification of the most cutting edge technologies able to support innovative teaching and learning approaches to ICH.